Adsorption of cyclic organics generated during electrochemical oxidation of Orange II by activated carbon fibres and toxicity test. (September 2015) - Li, Guoting; Feng, Yanmin; Chai, Xiaoqi; Yang, Ziyan; Zhang, Xiwang
Abstract: Though advanced oxidation processes are effective for the removal of organic pollutants in aqueous solution, generation of highly toxic cyclic organics emerges as one of their significant disadvantages. This study explored the adsorptive removal of cyclic organics generated during electrochemical oxidation of Orange II. It was observed that cyclic organics accumulated dramatically. In order to detoxify the toxicity of oxidation-treated effluent, activated carbon fibre was tentatively used to remove these cyclic organics. The adsorptive removal capability of activated carbon fibre declined with the prolonged oxidation duration. The removal efficiencies for both the dye and cyclic organics decreased with increasing solution pH. The increased reaction temperature reduced the uptake of cyclic intermediates, indicating an exothermic adsorption process. Moreover, the toxicity of the oxidation-treated effluent was significantly reduced by removing the cyclic intermediates via activated carbon fibre adsorption. Adsorption process might be a best alternative for the post-treatment process.